Prevalence and Risk Factors of Giardia lamblia Infection among Kindergarten Students in Mandangin Island, Sampang, Indonesia - Inggil Mukti Gunawan; Alpha Fardah Athiyyah; Heny Arwati (Universitas Airlangga, 2026)
Highlights: Low prevalence of giardiasis among kindergarten students. Good level of knowledge and personal hygiene practices of kindergarten children. Abstract Introduction: Giardiasis is a gastrointestinal disease caused by the parasite Giardia lamblia and affects many individuals in developing countries. Kindergarten children are at risk of Giardia infection due to limited knowledge and inadequate personal hygiene. This study aimed to determine the prevalence of G. lamblia infection among kindergarten children on Mandangin Island, Sampang, Indonesia. Methods: A cross-sectional study was performed between January and March 2023. Stool samples and questionnaires were collected from 37 participants to obtain data on their demographics, socioeconomic status, and behavioral risk factors. Giardia infection was diagnosed through direct stool examination and rapid antigen testing. The data were analyzed statistically using the International Business Machines Corporation (IBM) Statistical Package for the Social Sciences (SPSS) version 26.0, with p<0.05 considered statistically non-significant. Results: A total of 37 subjects were enrolled in this study. The prevalence of giardiasis was 5.4% (n=2) among the study population. There was no significant correlation between giardiasis infection and the risk factors examined (p>0.05). Conclusion: The low prevalence of giardiasis in this study may be attributable to the relatively high levels of knowledge and personal hygiene among the kindergarten children. In addition, the majority of residents of Mandangin Island, Sampang, Indonesia, used boiled rainwater for drinking. Access to safe drinking water, along with good personal hygiene practices, especially handwashing, can reduce the risk of giardiasis.